SOMATIC AND OTHER BIOLOGICAL ASPECTS OF COVID-19 VACCINATION: LEGAL MEASURES TO SUPPORT SOCIETY AND BUSINESS DURING THE POST-PANDEMIC ERA IN RUSSIA - Gulyaeva, Elena Evgenyevna; Trikoz, Elena Nikolaevna (Novos Estudos Jurídicos, 2021)
The purpose of the review is to comprehend the current trends in emergency rule-making in Russia and the restrictive practices introduced in the context of the COVID-19 pandemic. In response to new challenges, the Russian authorities have developed a kind of "rule-making vaccine". The introduction of new legislation, especially at the local level of Russian Federation, was accompanied by both long-term state support of business structures and the "freezing of the Russian economy." The situation of "unofficial testing" of a vaccine against COVID-19, facts of violation of the fundamentals of clinical trials, the norms of Russian legislation and generally recognized international standards in the field of clinical testing of drugs are analyzed. According to the position of the World Health Organization (WHO) the right to health imposes on the States a legal obligation to ensure timely access to adequate levels of high-quality health care, clean and safe drinking water, sanitation, adequate nutrition, shelter, health-related information and education, gender equality. As a result, the considerable amount of attention is paid to the analysis of the content of general and specific legal instruments at the national level to Support Society and Business During the Post-PandemicÂ  Era in Russia.